2023
DOI: 10.3389/fpls.2023.1238870
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing hybrid vigor: a comprehensive analysis of genetic distance and heterosis in eggplant landraces

Neha Rajan,
Sandip Debnath,
Kahkashan Perveen
et al.

Abstract: IntroductionThis study explored the molecular characterization of 14 eggplant (brinjal) genotypes to evaluate their genetic diversity and the impact of heterosis. As eggplant is a vital horticultural crop with substantial economic and nutritional value, a comprehensive understanding of its genetic makeup and heterosis effects is essential for effective breeding strategies. Our aim was not only to dissect the genetic diversity among these genotypes but also to determine how genetic distance impacts heterotic pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…Prediction of polygenic traits, such as those tested in this trial, is usually a major challenge in hybrid generation [ 56 ]. These results are similar to those found in other studies that have evaluated F 1 eggplant hybrids under water stress, where the responses were diverse and complex due to the genetic distance of the parents [ 16 , 57 ], the generation of hybrids with parents presenting moderate genetic distances could be a better strategy, as it has been seen that they achieve better results in eggplant [ 58 ]. At the growth level, the hybrids did not stand out in any trait under water stress, but it was observed that two hybrids had lower H 2 O 2 content, which could indicate a lower level of oxidative stress [ 59 ], and one hybrid had lower proline content, which could indicate a lower level of stress [ 60 ].…”
Section: Discussionsupporting
confidence: 89%
“…Prediction of polygenic traits, such as those tested in this trial, is usually a major challenge in hybrid generation [ 56 ]. These results are similar to those found in other studies that have evaluated F 1 eggplant hybrids under water stress, where the responses were diverse and complex due to the genetic distance of the parents [ 16 , 57 ], the generation of hybrids with parents presenting moderate genetic distances could be a better strategy, as it has been seen that they achieve better results in eggplant [ 58 ]. At the growth level, the hybrids did not stand out in any trait under water stress, but it was observed that two hybrids had lower H 2 O 2 content, which could indicate a lower level of oxidative stress [ 59 ], and one hybrid had lower proline content, which could indicate a lower level of stress [ 60 ].…”
Section: Discussionsupporting
confidence: 89%
“…Hybridizing these introduced materials with local varieties increases the chances of genetic diversity in sugarcane, enhancing the population’s adaptability to different environmental conditions [ 66 ] and contributing to broader adaptability and improved growth performance in various regions [ 67 ]. Combining introduced germplasms with local varieties promotes the incorporation of beneficial genetic factors in the offspring, leading to improvements in specific traits [ 68 ], such as enhanced resistance to biotic and abiotic stressors in sugarcane [ 69 , 70 ]. Genetic improvement could achieve superior performance in multiple aspects of new varieties.…”
Section: Discussionmentioning
confidence: 99%